Synthesis and Characterization of Five Bisoxime-Type Chelating Ligands Based on Bis(aminooxy)alkane and 2-Naphthaldehyde - Li1, Gang; Gao2, Su-Xia; Ren1, Zong-Li; Wen1, Na; Wang1, Li; Dong1, Xiu-Yan (Asian Journal of Chemistry, 2014)
Five bisoxime chelating ligands L1-L5 have been synthesized from 2-naphthaldehyde and 1,2-bis(aminooxy)ethane, 1,3-bis(aminooxy)-propane, 1,4-bis(aminooxy)butane, 1,5-bis(aminooxy)pentane and 1,6-bis(aminooxy)hexane in hot ethanolic medium, respectively and characterized by elemental analyses, IR, UV-visible spectra and 1H NMR spectroscopy. The bisoxime chelating ligands L1-L5 may be promising units for the construction of supramolecular metal complexes.